Kesalahan Penggunaan Huruf pada Fabel Anak “Seekor Kancil yang Selalu Ingat Tuhan” Karya Atisah - Zahra Azkiyah Syifa; Pasiha Nazwa Auniya; Shiffy Asyqil Qolbi; Khaerunnisa Khaerunnisa (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study aims to analyze the errors in word usage in the children’s fabels “Seekor Kancil yang Selalu Ingat Tuhan” by Atisah, with a focus on how these errors impact the educational value of the story. The fabels, intended for elementary school readers, carries significant moral lessons but presents linguistic challenges due to certain errors in vocabulary, grammar, and sentence structure. These errors include the use of technical terms, uncommon words, and overly formal expressions that may hinder comprehension for young readers. Using a descriptive quantitative method, the research collects data through documentation and error classification based on linguistic theories in morphology, syntax, and semantics. The findings reveal that while the fabels employs imaginative storytelling to convey moral lessons, some linguistic inconsistencies, such as redundant phrases, inappropriate vocabulary, and lack of contextual explanations, reduce its effectiveness. Recommendations include simplifying language, ensuring alignment with children’s cognitive levels, and providing contextual definitions for complex terms. These efforts aim to enhance the readability and educational value of children’s literature while fostering linguistic development.